The effectiveness of augmented reality in developing academic achievement and critical thinking for high school female students in Dammam and their attitudes towards it - Alghamdi, Eman Embarak Abdullah; Kotb, Eman Mohamed Mabrouk (Journal of Educational and Psychological Sciences, 2020)
The research aims to reveal the effectiveness of augmented reality in developing academic achievement and critical thinking for high school female students in Dammam Governorate in the Kingdom of Saudi Arabia and their attitudes towards it in the library and research course, The researcher used the descriptive and semi-experimental approaches, the research sample consisted of (44) female students from the first secondary class students, they were divided into two groups, the experimental group and their number (22) students use augmented reality, and the control group and their number (22) students use traditional education, the research used three tools represented in the achievement test, the scale of critical thinking, and the scale of trends, the research found that there are statistically significant differences at the level of significance (0.05 ≥ α) between the mean scores of students of the experimental group that use (augmented reality) and students of the control group that use (traditional education) in the post-application of the achievement test and the scale of critical thinking in favor of the experimental group, also, there are statistically significant differences at the significance level (0.05 ≥ α) between the mean scores of the students of the experimental group that use (augmented reality) in the pre and post application of the scale of trends in favor of the post application, the research recommended the necessity of using augmented reality technology in teaching library material and research in particular and the higher-order thinking skills included in the various subjects in general.